Self-reported skin problems and the healthy worker effect in the general working population of Norway: a three-year prospective study - Jose H Alfonso; Håkon A Johannessen (Nordic Association of Occupational Safety and Health (NOROSH), 2019)
OBJECTIVES: This study aimed to assess whether the occurrence of skin problems in 2006 (baseline) was associated with response frequency, quitting a job due to health problems, and change in occupational skin exposures in 2009. METHODS: We conducted a three-year prospective study of the general working population of Norway. Associations between baseline indicators (sex, age, education, occupation), and occurrence of skin problems with response frequency at follow-up were assessed with Chi-square test and unconditional logistic regression. Associations between the occurrence of skin problems at baseline with quitting a job due to health problems and skin exposure at follow-up were also assessed with unconditional logistic regression. RESULTS: We found no evidence of an association between the occurrence of skin problems at baseline and a lower response frequency at follow-up. Age, sex, education, and occupation were the most important predictors for response at follow-up. Skin problems at baseline consistently predicted quitting a job due to health problems at follow-up. No evidence of change in the patterns of occupational skin exposures at follow up in 2009 was found for workers reporting skin problems in 2006. CONCLUSION: While skin problems at baseline were not related to a lower response frequency at follow-up, our results suggest that workers reporting skin problems may quit their jobs due to health problems. Preventive efforts are still needed to reduce hazardous occupational skin exposures among workers reporting skin problems.